Intersecting feminism: gender, identity, and liberation in their eyes were watching God and The God of Small Things - Tabassum, Ahana (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2023.